Удосконалення технології обліку дебіторської заборгованості на підприємстві - Шум, М. А.; Потапова, Н. О. (НТУ "ХПІ", 2015)
Запропоновані напрями удосконалення технології обліку дебіторської заборгованості на підприємстві, а саме необхідність коригування законодавчих актів щодо віднесення витрат, понесених внаслідок нарахування резерву сумнівних боргів. Розроблено відомість визнання необхідності нарахування резерву сумнівних боргів. Наведено авторський поділ поточної дебіторської заборгованості згідно з договорами за строками непогашення. Встановлена необхідність надання повної інформації про дебіторську заборгованість підприємства відповідно до нормативних документів.

Directions of improvement of technology account receivables in the company, namely the need to adjust legislation to classify expenses incurred as a result of the accrual of provision for doubtful debts. Designed statement recognizing the need to accrue a reserve for doubtful debts. Present author separation current receivables under contracts in terms of default. Established the need to provide complete information about the company receivables in accordance with the regulations. Based on the analysis technology to improve accounting receivables in the company can offer such arrangements. First, it is desirable to amend the Tax Code regarding the attribution of costs incurred as a result of the accrual of provision for doubtful debts to other operating expenses. Secondly, you have to create a reserve for doubtful current receivables for goods, works and services. Third, implement the activities of enterprises in compiling the information necessary recognition of calculating the allowance for doubtful debts for the formation of legally correct documents on accounting for receivables in the company. Fourth, distribute current receivables under contracts in terms of default as follows: Group 1 - outstanding term of 1 month; Group 2 - term delinquency from 1 to 3 months; Group 3 - non-period of 3 to 6 months; Group 4 - term delinquency from 6 to 12 months; Group 5 - term default over a year. This distribution will allow to determine the need for calculating the allowance for doubtful debts. Fifth, establish the need to provide complete information about the company receivables according to P (S) 10. This company should provide information in any form in the notes to the financial statements.
Improving technology accounting receivables in the company
Keywords: резерв сумнівних боргів; технологія обліку; фінансова звітність; кредитування дебітора; accounts receivable; allowance for doubtful debts; technology; accounting; financial statements